2022
DOI: 10.3390/molecules27092795
|View full text |Cite
|
Sign up to set email alerts
|

Binary Effects of Gynostemma Gold Nanoparticles on Obesity and Inflammation via Downregulation of PPARγ/CEPBα and TNF-α Gene Expression

Abstract: Nanoscience is a multidisciplinary skill with elucidated nanoscale particles and their advantages in applications to various fields. Owing to their economical synthesis, biocompatible nature, and widespread biomedical and environmental applications, the green synthesis of metal nanoparticles using medicinal plants has become a potential research area in biomedical research and functional food formulations. Gynostemma pentaphyllum (GP) has been extensively used in traditional Chinese medicine to cure several di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Concisely, 100 μl of supernatant was mixed with 100 μl of Griess reagent. Finally, the absorbance was measured using a microplate reader (Bio-Tek Instruments, Inc.) at 540 nm ( Akter et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Concisely, 100 μl of supernatant was mixed with 100 μl of Griess reagent. Finally, the absorbance was measured using a microplate reader (Bio-Tek Instruments, Inc.) at 540 nm ( Akter et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Two types of AuNPs stated before were reported to exert a negative effect on the PPARg/CEBPa signalling pathways. 27,28 P.g AuNPs strongly decreased the mRNA expression levels of various adipogenic genes engaged in the STAT3/ PPARg/CEBPa pathways and significantly decreased the levels of PPARg and CEBPa, two crucial transcriptional factors in adipogenesis. 27 Moreover, GP-AuNPs notably inhibited the PPARg and C/EBPa expression in a dose-dependent manner, thus decreasing lipid accumulation and suppressing adipogenesis of 3T3-L1 cells.…”
Section: The Mechanisms Of Aunps For Osteogenic/adipogenic Regulationmentioning
confidence: 98%
“…27 Moreover, GP-AuNPs notably inhibited the PPARg and C/EBPa expression in a dose-dependent manner, thus decreasing lipid accumulation and suppressing adipogenesis of 3T3-L1 cells. 28 Furthermore, a previous study revealed the correlation between the PPARg gene and bone formation. 90 Chitosan AuNPs were conjugated with PPARg cDNA, and then introduced on titanium mini-implant surfaces for PPARg release to rat mandibular.…”
Section: The Mechanisms Of Aunps For Osteogenic/adipogenic Regulationmentioning
confidence: 99%
See 2 more Smart Citations